Treatment for hepatocellular carcinoma in the caudate lobe: a report of 13 cases - Zhang, Wei; Wu, Yakun; Li, You; Gong, Jianping; Long, Hao (International Surgery Journal, 2017)
Background: To investigate therapies of hepatocellular carcinoma in the caudate lobe, surgical approach and method, surgical outcome of hepatic caudate lobotomy. Methods: Clinical data of 13 patients with hepatocellular carcinoma in the caudate lobe who received surgical treatment in the Department of Hepatobiliary Surgery of the Second Affiliated Hospital of Chongqing Medical University from Jan 2010 to Jan 2014 was retrospectively analyzed. Results: Two patients selected TACE therapy. However, tumor metastasis was observed on them in short term, and the therapeutic effect was poor after several times of treatment. Nine patients received surgical treatment. Surgical approaches included left approach, right approach and combined approaches from the left and right side; surgical method was part or complete caudate lobe resection combining with other liver segments. The operation time was 220.0-350.0 minutes, with the average value of 259.4 minutes. The vascular clamping time was 21.0-45.0 minutes, with the average value of 30.2 minutes. The bleeding volume was 400.0-1800.0 ml, with the average value of 844.4 ml. In all patients, there was no perioperative death and no postoperative liver failure happened, and 4 patients who suffered from interrelated complications were cured or got better by conservative treatments. All patients were followed up for 24 months. The recurrent rates of 1 and 2-year were 44.4%, 88.9% respectively, and the survival rates of 1 and 2 year were 66.7%, 44.4% respectively after surgical resection. Conclusions: Resection is still the preferred therapeutic method for hepatocellular carcinoma in the caudate lobe. However, long-term outcomes of the therapy for hepatocellular carcinoma in the caudate lobe need further improvement.